Overview of Iron-Coated Dynamic Membrane for Water Treatment - Idriss, Ibrahim Maina; Isah, Umar Abdullahi; Lawan, Daggash Muhammad; Atiku, Kaka Goni; Hashmi, Zubair (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
The increasing global demand for clean and potable water has prompted the exploration of innovative water treatment technologies. Pre-deposited dynamic membrane systems, a novel approach in wastewater treatment, have gained attention due to their versatility and effectiveness. This mini-review focuses on the application of iron oxide-based dynamic membranes in water treatment processes. It discusses the impact, formation, properties, and various water treatment applications of iron oxide dynamic membranes, highlighting their potential to revolutionize the field of sustainable water treatment.